Third International Electronic Conference on Medicinal Chemistry (ECMC-3) - Mayence, Annie (Pharmaceuticals (Basel), 2018)
The third International Electronic Conference on Medicinal Chemistry, organized and sponsored by MDPI AG, publisher, and the journal Pharmaceuticals, took place in November 2017 on the SciForum website (www.sciforum.net/conference/ecmc-3). Around 300 authors from 34 different countries participated at the event, which hosted more than 70 presentations, keynotes, videos, and posters. A short description of some works presented during that scientific meeting is disclosed in this report.